Structural and biological aspects of natural bridged macrobicyclic peptides from marine resources. Issue 8 (29th April 2021) - Dahiya, Rajiv; Dahiya, Sunita; Kumar, Priyank; Kumar, Radhika V.; Dahiya, Saurabh; Kumar, Suresh; Saharan, Renu; Basu, Paramita; Mitra, Arindam; Sharma, Ajay; Kashaw, Sushil K.; Patel, Jayvadan K.
Abstract: Among peptide‐based drugs, naturally occurring bicyclic compounds have been established as molecules with unique therapeutic potential. The diverse pharmacological activities associated with bicyclic peptides from marine tunicates, sponges, and bacteria render them suitable to be employed as effective surrogate between complex and small therapeutic moieties. Bicyclic peptides possess greater conformational rigidity and higher metabolic stability as compared with linear and monocyclic peptides. The antibody‐like affinity and specificity of bicyclic peptides enable their binding to the challenging drug targets. Bridged macrobicyclic peptides from natural marine resources represent an underexplored class of molecules that provides promising platforms for drug development owing to their biocompatibility, similarity, and chemical diversity to proteins. The present review explores major marine‐derived bicyclic peptides including disulfide‐bridged, histidinotyrosine‐bridged, or histidinoalanine‐bridged macrobicyclic peptides along with their structural characteristics, synthesis, structure–activity relationship, and bioproperties.The comparison of these macrobicyclic congeners with linear/monocyclic peptides along with their therapeutic potential are also briefly discussed. Abstract : Natural bridged macrobicyclic peptides (BMPs) from marine resources form one of the most promising platforms for drug development owing to their biocompatibility and chemical diversity. This review provides a summary of the structural characteristics, synthesis routes, structure–activity relationships, and bioproperties of natural bioeffective BMPs from marine tunicates, sponges, and bacteria.